Therapeutic potential of secondary metabolites of Pleurotus ostreatus with cardiovascular disease-related receptors through in-silico methods - L. J. Hernandez; E. F. Flores; S. A. Laja; H. A. Gonzaga; S. M. Firmacion; C. Ibus; L. M. Lat; E. A. Cano (Regulatory Mechanisms in Biosystems, 2025)
Cardiovascular diseases (CVDs) remain the leading cause of mortality worldwide. In the search for safer therapeutic altern a tives, natural products have sparked pharmaceutical interest. Pleurotus ostreatus (oyster mushroom), which has been reported to improve glucose and lipid metabolism, blood pressure, and appetite, is a source of essential nutrients found on hardwood trees containing medicinal bioactive compounds such as lovastatin, 9,12-octadecadienoic acid, stigmasta-5,22-dien-3-ol, and gamma-sitosterol. This study investigated the therapeutic potential of secondary metabolites of P. ostreatus through in-silico methods. Molecular docking studies and visualization were performed using PyRx and BIOVIA Discovery Studio 2024, respectively, while Absorption, Distribution, Metabolism, Excretion, and Toxicity (ADMET) profiling was conducted using ADMET 3.0 LAB and SwissAdme to assess the pharmacokinetic properties of the compounds. Furthermore, the study employed lovastatin as the reference drug for determining the favorable characteristics of the other phytochemicals. The averaged receptor-ligand co m plexes demonstrated that stigmasta-5,22-dien-3-ol delineated the strongest binding interaction ( – 8.74 kcal/mol) with the card i ovascular receptors, followed by gamma-sitosterol ( – 8.40 kcal/mol), lovastatin ( – 8.13 kcal/mol), and 9,12-octadecadienoic acid ( – 6.0 kcal/mol). Surpassing lovastatin in terms of binding affinities, stigmasta-5,22-dien-3-ol, and gamma-sitosterol significantly demonstrated potential inhibitory effects in the overall regulation of cardiovascular function. ADMET profiling showed lovast a tin to have the most balanced profile. Although stigmasta-5,22-dien-3-ol and gamma-sitosterol demonstrated high plasma protein binding affinity and strong lipid solubility, it still required pharmacokinetic optimization to overcome poor absorption and rapid clearance. Concurrently, 9,12-octadecadienoic acid indicated outstanding biosystemic availability, although its use requir es pr o longed systemic caution. The findings of molecular docking coupled with ADMET analysis suggest P . ostreatus could potentia l ly provid e natural therapeutics for hypertension, dyslipidemia, and metabolic syndrome, warranting further exploration and co n firmation for efficacy and safety.